The challenges of implementing decentralisation: recent experiences in Uganda - Onyach-Olaa, Martin (2003)
Decentralisation, which began in Uganda in 1993, has increased opportunities for citizens to democratically determine how they should be governed and to make choices regarding the type and quality of public services they want. Citizens are now empowered to elect on a periodic basis persons whom they think can serve their interests on local councils. These changes have caused a major realignment in central - local relations. Some of the most important reforms have been led by the District Development Programme and the Local Government Development Programme, which are a focus on this article. Since the process began, numerous achievements have been realised in terms of improving governance and service delivery through democratic participation and community involvement. Despite these achievements, Uganda still faces a number of major challenges in deepening and institutionalising decentralisation. These challenges include, among others, technical capacity deficiencies in local governments and tensions among key stakeholders competing to maximise their role in decentralisation. - Reproduced.
Keywords: Decentralization - Uganda; Decentralization